Good Corporate Governance as Prevention of Credit Fraud at Government Bank - Kurniamaylani, Widia; Amir, Vaisal; Prasaja, Mukti (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
This study aims to determine the application of Good Corporate Governance as fraud prevention in providing briguna loans to PT Bank Rakyat Indonesia (Persero) Tbk Ngawi Branch office. This study used qualitative descriptive method by taking data derived from interviews and direct observations with officers of PT BRI and interviews with customers. Data collection is done by observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusions. The results of this study show that PT Bank Rakyat Indonesia (Persero) Tbk Ngawi Branch Office has applied GCG principles adequately in providing briguna loans. With the implementation of GCG principles, Bank BRI has carried out fraud prevention.